The 434(G > C) polymorphism in the eosinophil cationic protein gene and its association with tissue eosinophilia in oral squamous cell carcinomas - Pereira, Michele C.; Oliveira, Denise T.; Olivieri, Eloisa H. R. [UNESP]; Rogatto, Silvia Regina [UNESP]; Carvalho, Andre L.; Landman, Gilles; Kowalski, Luiz P. (Wiley-Blackwell Publishing, Inc, 2010)
Objective: The aim of this study was to investigate the prevalence of the Eosinophil cationic protein (ECP)-gene polymorphism 434(G > C) in oral squamous cell carcinoma (OSCC) patients and its association with tumor-associated tissue eosinophilia (TATE), demographic, clinical, and microscopic variables. Methods: The ECP genotypes of 165 healthy individuals and 157 OSCC patients were detected by PCR-RFLP analysis after cleavage of the amplified DNA sequence with enzyme PstI. TATE was obtained by morphometric analysis. Chi-square test or Fisher's exact test was used to analyze the association of ECP-gene polymorphism 434(G > C) with TATE, demographic, clinical, and microscopic variables in OSCC patients. Disease-free survival and overall survival were calculated by the Kaplan-Meier product-limit actuarial method and the comparison of the survival curves were performed using log rank test. Results: Most of healthy individuals (53.33%) and OSCC patients (57.97%) were heterozygous for the ECP 434(G > C) polymorphism. Based on numerical differences, our results showed that OSCC patients with intense TATE and at least one C allele had a higher frequency of bilateral neck dissection, local recurrence, vascular embolization, involved resection margins, and postoperative radiotherapy. No statistically significant differences on survival rates were found in OSCC patients presenting different ECP 434(G > C) genotypes. Conclusions: These results suggest a tendency towards a poor clinical outcome in OSCC patients with intense TATE and 434GC/CC genotypes, probably due to an ECP genetic variant with altered cytotoxic activity.
Keywords: eosinophil cationic protein; eosinophils; gene polymorphism; prognosis; squamous cell carcinoma